(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study is to determine the frequency of encountering anomalous vessels in liver bed and mode of hemostasis to stop bleeding from these vessels. Material and Methods: This observational cross sectional study was conducted from 01-08-2012 to 31-07-2016 in the Department of surgery of Mayo Hospital, Lahore. Results: A total of 451 cases were included having mean age of 37.10 ± 10.26 years. There were 347 (77%) females and 104 (33%) males. Gallstones were found in 424 (94%) patients and 27 (6%) patients had no gallstones. There were 98 (22%) acute on chronic cases and 353 (78%) chronic cases. The incidence of anomalous vessels in liver bed was 21%. Out of 95 cases with anomalous vessels, 65 (69%) had acute on chronic attack in past one week. Bleeding from liver bed was seen in 59 cases (13.1%). The hemostatic efficacy was 100% with endoclip technique and 83% with direct pressure application. In 9 patients direct pressure was not sufficient so endo-suturing was done. Conclusion: Per-operative incidence of anomalous vessels in liver bed is higher in acute on chronic presentation. Careful dissection of liver bed can prevent bleeding from these vessels.